2018
DOI: 10.3390/g9040073
|View full text |Cite
|
Sign up to set email alerts
|

Does Implicit Bias Predict Dictator Giving?

Abstract: Implicit associations and biases are carried without awareness or conscious direction, yet there is reason to believe they may be influenced by social pressures. In this paper, I study social pressure as a motive to give, as well as giving itself under conditions of implicit bias. In doing so, I pair the Implicit Association Test (IAT), commonplace in other social sciences, with a laboratory dictator game with sorting. I find that despite its popularity, the IAT does not predict dictator giving and social pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Most existing work on implicit biases and prosocial behavior have focused on racial biases and attitudes. For example, while some studies found that implicit color bias or implicit prejudice toward Black reduces giving and prosocial behavior (e.g., Bhati, 2021; Stepanikova et al, 2011), others found that implicit bias does not predict giving in a dictator game experiment (e.g., Lee, 2018). Although researchers have studied attitudes toward the poor (e.g., Cozzarelli et al, 2001), they have exclusively relied on self-reported explicit measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most existing work on implicit biases and prosocial behavior have focused on racial biases and attitudes. For example, while some studies found that implicit color bias or implicit prejudice toward Black reduces giving and prosocial behavior (e.g., Bhati, 2021; Stepanikova et al, 2011), others found that implicit bias does not predict giving in a dictator game experiment (e.g., Lee, 2018). Although researchers have studied attitudes toward the poor (e.g., Cozzarelli et al, 2001), they have exclusively relied on self-reported explicit measures.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have examined attitudes and prosocial behavior, several gaps still remain. First, the majority of the studies on implicit biases and prosocial behavior have focused on racial biases and attitudes (e.g., Bhati, 2021; Brown-Iannuzzi et al, 2019; Lee, 2018; Stepanikova et al, 2011; Triplett, 2012). Others have studied implicit biases toward refuges (Weber et al, 2020), implicit biases about the rich and the wealthy (Horwitz & Dovidio, 2017; Zhou & Wang, 2007), and implicit independent and interdependent self-construal (Moscardino et al, 2020).…”
mentioning
confidence: 99%
“…Under meritocratic admissions, admission officers would decide on whether to admit applicant i in the current year, based on φ (X i , G i , Z i ), their subjective assessment of i's academic merit (e.g., how applicant i will perform when admitted). 3 In accordance with our economic model, we assume that applicant i with G i = g, Z i = z, and X i = x ∈ X g is offered admission (i.e., D i = 1) if and only if φ (x, g, z) ≥ γ, where γ denotes the university-wide baseline threshold for applicants-that is,…”
Section: A Econometric Modelmentioning
confidence: 99%
“…When there are multiple sources of soft information, Z may be interpreted as a composite scalar index (e.g., a weighted average) of these characteristics 3. In line with the existing literature on bias detection referenced above, we ignore issues about risk and leave that for future research.…”
mentioning
confidence: 99%